2022
DOI: 10.1021/acssuschemeng.2c03633
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy for Room Temperature Knitting of Sulfur in Polybenzoxazine: A New Class of Solution Processable Copolymers

Abstract: Industrial applications of the upcoming class of high-performance biobased polybenzoxazines are currently impeded by the requirement of high polymerization temperatures. Valorization of elemental sulfur (S8), petroleum waste, has provided attractive technological opportunities. However, achieving sulfur copolymers at a low temperature remains a challenging task. Here, a unique facile synthetic strategy was adopted to form a fully sustainable solution-processable benzoxazine-sulfur copolymer via a ring-opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…17c). 200 The obtained polysulfides showed good solubility in common organic solvents such as CHCl 3 , DMSO, o -DCB, THF, and toluene; however, at higher sulfur content (>90% S) and higher temperature, some insoluble material appeared, indicating some degree of crosslinking. Indeed, increasing the sulfur content and temperature increased the T g of the polysulfides from 10 to 86 °C (Fig.…”
Section: Natural Product Derived Polysulfidesmentioning
confidence: 91%
“…17c). 200 The obtained polysulfides showed good solubility in common organic solvents such as CHCl 3 , DMSO, o -DCB, THF, and toluene; however, at higher sulfur content (>90% S) and higher temperature, some insoluble material appeared, indicating some degree of crosslinking. Indeed, increasing the sulfur content and temperature increased the T g of the polysulfides from 10 to 86 °C (Fig.…”
Section: Natural Product Derived Polysulfidesmentioning
confidence: 91%
“…[13][14][15][16][17][18] Fully-sustainable sulfur composites can be prepared when petroleum-derived olens are replaced with biologically-produced monomers, such as fatty acids, [19][20][21] triglycerides, [22][23][24][25][26] terpenoids, 25,[27][28][29][30] amino acid derivatives, 31 lignin derivatives, [32][33][34][35] cellulose derivatives, 30,36 and even raw lignocellulosic biomass. 37,38 Reaction temperatures for preparing or shaping HSMs can be lowered by using catalysts, 39 mechanochemical methods, 40 ternary mixtures, 41 pre-formation of more reactive sulfur species, 42 using nucleophiles to fuse materials together through S-S metathesis, 43 or by compression-molding of materials. 44 Promising photochemical routes to C-S bond formation towards preparing or healing HSMs also hold potential for lowering the energy requirements of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Inverse vulcanization reported by Pyun and coworkers is a facile and powerful methodology to convert the abundant byproduct sulfur from petroleum industry into sulfur-rich polymers. In addition to petrobased feedstocks, biobased monomers have also been utilized to prepare inverse vulcanized polymers. Owing to the unique chemophysical properties arising from the high sulfur content, these materials show great potential for various applications, including the refractive index, Li–S battery cathodes, , self-healing materials, , heavy metal capture, , infrared imaging, and also injecting new vitality into rubber composites. Guo et al reported that the sulfur and styrene copolymers through inverse vulcanization as an efficient vulcanizing agent could cross-link diene rubbers in a green manner .…”
Section: Introductionmentioning
confidence: 99%